Pemodelan Standar Operasional Prosedur Pemeliharaan Dan Perawatan Komponen Arsitektural Kamar Fave Hotel Diponegoro Semarang - Ade Dwi Marsyida; Sugiharto Sugiharto; Martono Martono (Politeknik Negeri Semarang, 2018)
As a functioning building for public facilities, the building maintenance of components and utilities at FAVE Hotel Diponegoro Semarang are very important, related to the level of customer satisfaction and company performance. One of the main components to be considered in the hotel building is the performance of the rooms, because it determines the level of customer satisfaction. Therefore, it is necessary to have Standard Operating Procedure (SOP) about the maintenance and the treatment on terms and conditions. This research study about the standard operating procedure especially in the maintenance and the treatment of architectural component at FAVE Hotel Diponegoro Semarang. The author conducted direct interviews, identified the condition of the rooms’ arsitectural components, and distributed questionnaires to all hotel staff for strengthening the purpose of this study. The result of the questionnaire showed that the standardization of work is important in the implementation of the activities. After the SOP design was formed, the author tested the SOP in the field directly and spread the questionnaires to all hotel staff to conclude the response to the existence of the SOP. The results obtained 0% very less, 0% less, 3% enough, 15% good, and 83% very good, this is based on SOP generated in terms of tools, materials, and methods of implementation. Therefore, hopefully this research can give real contributions and positive effect to the performance of guest room of FAVE Hotel Diponegoro Semarang.Kata kunci : Standard Operating Procedure (SOP), maintenance, architecturalcomponents, hotel